Design of engine mounting for single seated educational racing vehicle - Abdul Munir, Fudhail; Sukri, Muhammad Izzat Syazwan; Syahrial, Fadhli; Roseli, Adnan; Dhar Malingam, Sivakumar; Hassan, Muhammad Zahir (Asian Research Publishing Network (ARPN), 2017)
The power train system for a single seated educational racing vehicle is consists of an engine and a transaxle. This power train unit is attached to the chassis frame of the vehicle. Therefore, it is desirable that both the engine and transaxle can be easily installed to the vehicle chassis frame. For a racing vehicle for educational competition, an adjustable engine mounting system is provided to allow for fine adjustment of the engine position and the transaxle. The alternative term for transaxle is called as the chain tension that includes a selective lock-out feature. This feature allows an operator to lock out the selected forward or reverse gears to alter the vehicle performance during racing. In this work, three design of engine mounts for the use of single-seated educational racing vehicle are proposed. The design process is carried out using CATIA V5 educational software. Once all the proposed designs of the engine mounts are completed, Finite Element Analysis (FEA) is performed. Furthermore, a modal analysis using ANSYS Workbench Release 16.0 is also conducted to determine the natural frequency of the component. The results suggest that the best design of engine mount is Design 2. This selection is based on the low natural frequency of the component.